2021
DOI: 10.1021/acs.jafc.1c04953
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Pesticide Activities of 2-Cyanoacrylate Derivatives

Abstract: 2-Cyanoacrylates are a unique class of compounds with high photosystem II electron transport inhibitory activity. Through the in-depth study of molecular design, synthesis, biological activity, structure−activity relationship, and action mechanism, a large number of 2-cyanoacrylate derivatives with excellent herbicidal activity were found. In addition, 2-cyanoacrylate derivatives with different substituents have also been found to have good fungicidal or anti-plant virus activities. To further guide the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Most compounds distinctly presented better inhibitory effects on dicotyledonous weeds than monocotyledonous weeds. Among them, the IC 50 of Compound 16a [ 41 ] (IC 50 = 0.041 mg/L), 16b [ 42 ] (IC 50 = 0.0262 mg/L), 17a [ 43 ] (IC 50 = 0.01937 mg/L), 17b [ 44 ] (IC 50 = 0.01252 mg/L), 18a [ 45 ] (IC 50 = 0.032 mg/L), and 18b [ 8 ] (IC 50 = 0.0468 μmol/L) against PPO was consistent with or better than that of oxyfluorfen. At 150 g a.i./ha, Compound 16a achieved 100% inhibition against A. theophrasti for post-emergence treatment.…”
Section: Herbicides Containing Phenoxypyridine Scaffoldmentioning
confidence: 99%
“…Most compounds distinctly presented better inhibitory effects on dicotyledonous weeds than monocotyledonous weeds. Among them, the IC 50 of Compound 16a [ 41 ] (IC 50 = 0.041 mg/L), 16b [ 42 ] (IC 50 = 0.0262 mg/L), 17a [ 43 ] (IC 50 = 0.01937 mg/L), 17b [ 44 ] (IC 50 = 0.01252 mg/L), 18a [ 45 ] (IC 50 = 0.032 mg/L), and 18b [ 8 ] (IC 50 = 0.0468 μmol/L) against PPO was consistent with or better than that of oxyfluorfen. At 150 g a.i./ha, Compound 16a achieved 100% inhibition against A. theophrasti for post-emergence treatment.…”
Section: Herbicides Containing Phenoxypyridine Scaffoldmentioning
confidence: 99%
“…These compounds have been found to exhibit a range of beneficial properties, such as anti-inflammatory, antimicrobial, antiviral, and antitumor activities, making them attractive targets for drug development 3 , 4 . Several methods for the preparation of biologically important 14-aryl-14H-dibenzo[a,j]xanthenes and 1,8-dioxo-octahydroxanthenes have been reported in the literature 5 – 8 , including the use of various catalysts or promoters 9 – 11 . However, most acid catalysts are highly corrosive and difficult to recover for subsequent reactions, which can limit their practical application 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The etoxazole analogues obtained from alcohols and phenols may have a good price advantage, even if they only maintain acaricidal activity, and the introduction of an oxygen atom into the substituent of the main skeleton is likely to improve the activity. For example, studies on the cyanoacrylate-type photosystem II electron transfer inhibitors have shown that ethoxyethyl esters have higher activity than the corresponding ethyl esters because the presence of oxygen increases the binding ability between the molecule and the target. , Therefore, to summarize the relationship between structure and activity and pursue more promising compounds, in this work, alkyl or phenyl ether moiety was introduced to the para site of the 4-phenyl of the 2,4-diphenyl-1,3-oxazolines ( I , Figure ). The synthesis, bioassay result (including acaricidal activity and insecticidal activity), and detailed structure–activity relationship are reported, and the scale synthetic route for the most promising acaricidal compound is also studied.…”
Section: Introductionmentioning
confidence: 99%